Expressão de hidrolases e produção de lipase por yarrowia lipolytica - Kleinert, Edmilson José (2020)
Lipases are a class of enzymes responsible for the hydrolysis of triacylglycerols in fatty acid and glycerol, requiring less energy to promote the reaction. They are applied to several areas of the industry: pharmaceutical, food, chemical, among others. The non-conventional yeast Yarrowia lipolytica can produce a variety of enzymes, including lipase, and therefore it is widely used in industry because it is safe for health. The aim of this work was to evaluate the ability of this yeast to produce lipases with industrial potential. For this, phenotypic screening tests were performed to assess lipolytic, proteolytic, amylolytic activity, esterase activity and submerged fermentation. Due to a better performance among the strains analyzed, Yarrowia lipolytica QU31 strain was used in subsequent tests. Lipase activities ranged from 0.7 to 2.7 U.ml-1, and the variables used did not have a significant influence on these values. None of the strains tested showed amylolytic nor proteolytic activity. In view of the low values found, the yeasts evaluated do not have a good potential to be applied in the industry.